2017
DOI: 10.1103/physrevb.95.125108
|View full text |Cite
|
Sign up to set email alerts
|

Breaking of SU(4) symmetry and interplay between strongly correlated phases in the Hubbard model

Abstract: We study the thermodynamic properties of four-component fermionic mixtures described by the Hubbard model using the dynamical mean-field-theory approach. Special attention is given to the system with SU(4)-symmetric interactions at half filling, where we analyze equilibrium many-body phases and their coexistence regions at nonzero temperature for the case of simple cubic lattice geometry. We also determine the evolution of observables in low-temperature phases while lowering the symmetry of the Hamiltonian tow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We studied the influence of spin symmetry (in particular, presence of the spin-flip term) in the interaction part of the Hamiltonian on the FM instability in the multiorbital Hubbard model by means of DMFT. We observe strong effects of suppression of FM phases when accounting for full spin-rotational symmetry in the two-orbital systems (in contrast to weaker effects for AFM ordering [19,21]). By considering the three-orbital model, it is shown that these effects become weaker (i.e., FM ordering effectively revives) with an increase of the number of active orbitals that agrees well with arguments based on suppression of quantum fluctuations due to approaching the limit of classical spins.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We studied the influence of spin symmetry (in particular, presence of the spin-flip term) in the interaction part of the Hamiltonian on the FM instability in the multiorbital Hubbard model by means of DMFT. We observe strong effects of suppression of FM phases when accounting for full spin-rotational symmetry in the two-orbital systems (in contrast to weaker effects for AFM ordering [19,21]). By considering the three-orbital model, it is shown that these effects become weaker (i.e., FM ordering effectively revives) with an increase of the number of active orbitals that agrees well with arguments based on suppression of quantum fluctuations due to approaching the limit of classical spins.…”
Section: Discussionmentioning
confidence: 71%
“…[10] for a recent material-oriented analysis). Therefore, a significant effort has been made to account for the full rotational symmetry of two-particle interactions [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…First, it is a simple limit of multi-orbital models such as those used to describe transition metal oxides [9][10][11], graphene's SU(4) spin-valley symmetry [12], and twisted-bilayer graphene [13][14][15][16][17]. Second, the SU(N ) FHM is predicted to display a variety of interesting and exotic phases even in very special limits, such as: the conventional N = 2 FHM, the N = 3 FHM [18][19][20][21][22][23][24][25][26][27], the N = 4 FHM at quarter filling [28,29], even values of N at half-filling [30][31][32][33][34][35][36][37], special N → ∞ limits [38][39][40][41][42], 1D chains [43][44][45][46][47][48][49], and the Heisenberg limit for N = 3, 4, 5 [10,26,[50][51][52][53]…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we provide such a proposal by presenting an analysis of the dynamics of a strongly interacting few-body system of fermions with SU( N ) symmetry after a sudden change - a quench - in the trapping potential. Recently, systems of cold atoms in optical lattices with SU(3) and SU(4) symmetries have been explored theoretically 43,44 . The correlations of SU( N ) impenetrable systems have also been calculated for an increasing number of internal components and display interesting properties 45 .…”
Section: Introductionmentioning
confidence: 99%